The Relationship of Physical Condition and Quality Of Life In Breast Cancer Survivors In Malang City - Dyah Widodo (Poltekkes Kemenkes Malang, 2021)
Carcinoma Mammae or breast cancer is a malignancy in breast tissue. Breast cancer in women is most frequently diagnosed throughout the world and is one of the most common types of cancer in Indonesia. The aims of this study were 1) to explore physical condition and quality of life in breast cancer survivors; 2) analyze the relationship between physical condition and quality of life in breast cancer survivors; The research method is correlation, with a sample size of 158 people according to the inclusion criteria, research was conducted in East Java, using questionnaire research instruments, interview sheets and observation sheets. The data analysis is descriptive statistical analysis and correlation with alpha 0.5. The results showed that the majority of respondents experienced physical problems, hair loss (77.2%), feeling weak or easily tired (72.8%), nausea, vomiting (45.6%), blackened skin and nails, 46.8% and 41.1% respectively, and sleep disorders. (38.6%); Quality of life in breast cancer survivors shows an average score of 80.94, which is in a good quality of life position. It was concluded that there was a relationship between physical condition and quality of life in breast cancer survivors (sig.0.003). Physical condition needs to be maintained so that the quality of life of breast cancer survivors remains good.